Influence of magnesium-to-phosphate ratio and water-to-cement ratio on hydration and properties of magnesium potassium phosphate cements. (September 2019) - Xu, Biwan; Winnefeld, Frank; Kaufmann, Josef; Lothenbach, Barbara
Abstract: Magnesium-to-phosphate (Mg/PO4 ) and water-to-cement (w/c) ratios are important factors controlling hydration and properties of magnesium potassium phosphate (MKP) cements. This study investigated the influence of Mg/PO4 molar ratios (2.7, 4 and 8) and w/c (0.25 and 5) on cement hydration, compressive strength and volume stability. Low w/c ratio slowed down cement hydration at lower Mg/PO4 beyond 1 day, and prevented the precipitation of intermediate hydrates at higher Mg/PO4 . At lower Mg/PO4 expansion and strength loss were observed with time due to the continuing hydration within the already hardened cement. Higher Mg/PO4 resulted in faster hydration, higher strength, and in the precipitation of traces of brucite, which had no significant influence on the long-term volume stability and strength. Therefore, moderate Mg/PO4 molar ratios between 4 and 8 depending on w/c ratio used are recommended for the production of MKP cements with robust performance.